Ghana - Women's Role in Improved Economic Performance - World Bank (Washington, DC, 2012)
The Government of Ghana's program to develop a gender strategy has been supported by the World Bank. This article is based on a Bank-assisted sector study, Ghana: gender analysis and policymaking for development. The Bank team worked closely with Ghanaian Ministries of Agriculture, Micro-finance, Education, and Health to identify gender issues and study feasible recommendations. Along with the government, a broad range of stakeholders participated in the study, including academic institutions, non-governmental organizations, and women's groups. Through workshops and mission visits, four points of focus were identified for the study: agriculture, micro-enterprises, education, and health. Many of the stakeholders also emphasized the importance of strengthening Ghana's institutional capacity to develop and implement policies that adequately address gender concerns. The study focuses on two broad areas of gender-based differences and inequalities: the links between gender and economic productivity, and the development of human capital. In addition to the study described here, the Ghanaian government produced two policy documents from this study; both are now under final review within the government.